ANALISIS LAYANAN PEDULILINDUNGI DENGAN MODEL UKUR E-GOVQUAL - Sesilia Tiara Rahayu Ada; Fiqi Akbar Trinanda; Divane Infonya Safinatunnajah; Laksamana Fajar Phumi; Tri Lathif Mardi Suryanto (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
Technological developments are increasing periodically affecting society in interacting. In the Covid-19 era, public services provided by the government for the community have become more accessible through the internet. Government services that are applied to the world of technology are called E-government. In the Covid-19 era, technology is needed to help people access a location or travel. Due to this, the Government of the Republic of Indonesia issued the Peduli Lindungi application as a form of prevention and monitoring of the spread of Covid-19 and the national vaccination program. The purpose of this application is to tackle the spread of Corona Virus Disease (Covid-19) and other diseases. In this application, people need to access a barcode to access certain places, so that every movement is monitored. This journal was created in order to measure the level of service quality on protect care using various measurement methods with the e-GovQual measurement model, which is one of the measurement techniques to determine the quality of government website services. Due to the high number of Covid-19 cases, the "PeduliLindungi" application is required to have good services and benefits and is easily accessible, therefore in this journal researchers will measure how effective the application can be.